Nisbah kelamin dan pola peletakan telur parasitoid Trichogramma chilotraeae Nagaraja & Nagarkatti (Hymenoptera: Trichogrammatidae) pada berbagai jumlah inang - hasriyanty hasriyanty; Damayanti Buchori; Pudjianto Pudjianto (Perhimpunan Entomologi Indonesia, 2007)
The objective of the research was to study sex ratio and oviposition sequence of egg parasitoid Trichogramma chilotraeae in relation with host density under laboratory condition. Parasitoid response with respect to oviposition sequence was examined by exposing five different host (egg) densities: 3, 6, 12, 24 and 48 on female parasitoids T. chilotraeae. Results showed that in general, female parasitoid laid its female progeny at the beginning of oviposition sequence. Host density was found to have a strong effect on sex ratio. Sex ratio increase with increasing of host number.